Quantification of 1‐(propan‐2‐ylamino)‐4‐propoxy‐9H‐thioxanthen‐9‐one (TX5), a newly synthetized P‐glycoprotein inducer/activator, in biological samples: method development and validation. (21st September 2016) - Ferreira, Ana Filipa; Ponte, Filipa; Silva, Renata; Rocha‐Pereira, Carolina; Sousa, Emília; Pinto, Madalena; Bastos, Maria de Lourdes; Remião, Fernando
Abstract: A simple, rapid and economical method was developed and validated for the analysis and quantification of 1‐(propan‐2‐ylamino)‐4‐propoxy‐9 H ‐thioxanthen‐9‐one (TX5), a P‐glycoprotein inducer/activator, in biological samples, using reverse‐phase high‐performance liquid chromatography (HPLC). A C18 column and a mobile phase composed of methanol–water (90/10, v /v) with 1% (v/v) triethylamine, at a flow rate of 1 mL/min, were used for chromatographic separation. TX5 standards (0.5–150 μm ) were prepared in human serum. Methanol was used for TX5 extraction and serum protein precipitation. After filtration, samples were injected into the HPLC apparatus and TX5 was quantified by a conventional UV detector at 255 nm. The TX5 retention time was 13 min in this isocratic system. The method was validated according to ICH guidelines for specificity/selectivity, linearity, accuracy, precision, limits of detection and quantification (LOD and LOQ) and recovery. The method was proved to be selective, as there were no interferences of endogenous compounds with the same retention time of TX5. Also, the developed method was linear ( r 2 ≥ 0.99) for TX5 concentrations between 0.5 and 150 μm and the LOD and LOQ were 0.08 and 0.23 μm, respectively. The results indicated that the reported method could meet the requirements for TX5 analysis in the trace amounts expected to be present in biological samples.